Jackson Pollock - Frank, Elizabeth, 1945-; Pollock, Jackson, 1912-1956 (New York : Abbeville Press, 1983)
Discusses the life and work of Jackson Pollack
Introduction -- Beginnings, 1912-30 -- New York, 1930-41 -- Arrival, 1942-46 -- Springs, 1947-50 -- The black paintings, 1950-53 -- Terminus, 1953-56 -- Aftermath -- Artist's statements -- Notes on techniques
Cover title: Pollock
Includes bibliographical references (pages 123-126) and index
Keywords: Pollock, Jackson, -- 1912-1956; Painters -- United States -- Biography